2000
DOI: 10.1038/sj.onc.1203315
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase-related protein 2 as a mediator of melanoma specific resistance to cis-diamminedichloroplatinum(II): therapeutic implications

Abstract: A major obstacle in the systemic treatment of advanced malignant melanoma is its intrinsic resistance to conventionally used chemotherapeutic agents. In order to investigate the mechanisms of this intrinsic resistance, we have previously utilized retroviral insertional mutagenesis on an early-stage, drug sensitive human melanoma cell line (WM35) to establish mutated cell lines that exhibited increased resistance to cis-diamminedichloroplatinum(II) (CDDP). Here, we demonstrate that this increased resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
(30 reference statements)
4
51
0
Order By: Relevance
“…Our study showed that TRP-2 overexpression cell line TRP-2-U373 increased resistance to both carboplatin and temozolomide. This finding was consistent with a previous report that TRP-2 overexpression increased specific resistance to DNAdamage drugs including carboplatin and methotrexate in melanoma (Chu et al, 2000). In general, multidrug resistance (MDR) is a serious problem associated with chemotherapy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our study showed that TRP-2 overexpression cell line TRP-2-U373 increased resistance to both carboplatin and temozolomide. This finding was consistent with a previous report that TRP-2 overexpression increased specific resistance to DNAdamage drugs including carboplatin and methotrexate in melanoma (Chu et al, 2000). In general, multidrug resistance (MDR) is a serious problem associated with chemotherapy.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, there were some reports that TRP-2 overexpression was associated specifically with resistance to DNA-damaging drugs and radiation treatment (Chu et al, 2000;Pak et al, 2000Pak et al, , 2001Pak et al, , 2004. We also reported recently that compared to patients receiving either chemotherapy or vaccinations alone, glioblastoma patients who received chemotherapy after active immunological DC-based vaccination experienced slower tumor progression and longer survival times .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It was even reported that the presence of DCT in melanoma is correlated with resistance to certain chemotherapeutic agents (8 ) will affect melanoma formation or melanoma sensitivity. This can now be tested by using Dct mutant and knockout mice following breeding with transgenic melanoma models.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge facing chemotherapy of melanoma that has limited treatment efficacy is resistance to conventional chemotherapy regimens (3,4). Cisplatin is recommended for melanoma patients routinely (5).…”
Section: Introductionmentioning
confidence: 99%